Expanding Robotic Arm-Assisted Knee Surgery: The First Attempt to Use the System for Knee Revision Arthroplasty - Dimitrios Kalavrytinos; Christos Koutserimpas; Ioannis Kalavrytinos; Konstantinos Dretakis (Case Reports in Orthopedics)
Robotic arm-assisted arthroplasty was introduced in 2006 and has expanded its applications into unicompartmental knee, total knee, and total hip replacement. The first case of a revision surgery from conventional unicompartmental to total knee arthroplasty with the utilization of the robotic arm-assisted MAKO system is presented. An 87-year-old female presented with deteriorating left knee pain due to failure of medial unicompartmental knee arthroplasty at the outpatient clinic. The patient was advised to undergo revision surgery. Through medial parapatellar arthrotomy, the joint was exposed. With the use of the MAKO system, the estimated depth of the medial plateau according to CT planning was found to be 10 mm more distal than the lateral. The resection line of the remaining plateau was placed deliberately 2 mm more distal in order to achieve satisfactory replacement of the bony gap of the medial tibial condyle by a 10 mm augment. The patient had an uneventful recovery. A plethora of additional applications in the future, such as total shoulder or reverse total shoulder arthroplasty, megaprosthesis placement in oncological patients, and total hip or knee revision surgeries, may improve patient-related outcomes.